Neuromarketing Applied to Educational Toy Packaging - Juarez, David; Tur-Viñes, Victoria; Mengual, Ana (Frontiers in Psychology, 2020)
This research work comes in response to the question of which aspects are more relevant for consumers in purchasing educational toys, which are different from other toys that are focused solely on leisure. This empirical research focuses on an educational toy distributed in Spain by Educa brand (Conector family, reference "I learn English"), which is the product with the highest demand of this brand, and analyses how consumers make decisions concerning this product in relation to other products designed by competitors. The research looks into customer reactions while looking at these products, measuring brain activity generated by different aspects of product design and its influence on choice. The aim of the present study was to propose a model that optimizes the communication design of educational toys packaging. Through the use of neuromarketing techniques –attention through eye tracking, and emotion using galvanic skin response– as well as qualitative research techniques, the objective of this research is to determine the motivations in the processes of buying educational toys. The packaging design elements analysed are brand, product family, toy name, recommended age, game image, number of questions / topics and additional texts. The results suggest that the most important elements are the graphic details of the packaging, obtaining a perception of a higher educational level as more questions are addressed by the game. The simultaneous combination of qualitative techniques monitored with galvanic skin response (neuro-qualitative study) allows additional conclusions to be aligned with the end user of the product, including a prominent social component when the product is purchased as a gift for a third party.